Dietary habits and Helicobacter pylori infection: a cross sectional study at a Lebanese hospital - Shafika Assaad; Rawan Chaaban; Fida Tannous; Christy Costanian (BMC Gastroenterology, 2018)
Abstract Background To examine the association between dietary habits and Helicobacter pylori (H. pylori) infection among patients at a tertiary healthcare center in Lebanon. Methods This cross-sectional study was conducted on 294 patients in 2016, at a hospital in Northern Lebanon. Participants were interviewed using a structured questionnaire to collect information on socio-demographic and lifestyle characteristics; dietary habits were ascertained via a short food frequency questionnaire (FFQ). H. pylori status (positive vs. negative) was determined after upper GI endoscopy where gastric biopsy specimens from the antrum, body, and fundus region were collected and then sent for pathology analysis. Multivariable logistic regression was conducted to identify the association between socio-demographic, lifestyle, dietary and other health-related variables with H pylori infection. Results The prevalence of H. pylori infection was found to be 52.4% in this sample. Results of the multivariable analysis showed that H. pylori infection risk was higher among participants with a university education or above (OR = 2.74; CI = 1.17–6.44), those with a history of peptic ulcers (OR = 3.80; CI = 1.80–8.01), gastric adenocarcinoma (OR = 3.99; CI = 1.35–11.83) and vitamin D level below normal (OR = 29.14; CI = 11.77–72.13). In contrast, hyperglycemia was protective against H. pylori (OR = 0.18; CI = 0.03–0.89). No relationship between dietary habits and H. pylori infection was found in the adjusted analysis. Conclusions Socio-demographic and clinical variables are found to be associated with H. pylori, but not with dietary factors. Further studies are needed to investigate the effect of diet on H. pylori risk.